2017
DOI: 10.1186/s12872-017-0485-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum transaminases with short- and long-term outcomes in patients with ST-elevation myocardial infarction undergoing primary percutaneous coronary intervention

Abstract: BackgroundAlanine transaminase (ALT) and aspartate aminotransferase (AST) are referred to as liver transaminases. Although used routinely in clinical practice for decades, their role as predictors of mortality has not been examined until recently. We studied the predictive value of these serum transaminases in patients with ST-segment elevation myocardial infarction (STEMI) treated with primary percutaneous coronary intervention (PCI).MethodsWe analyzed records of 2417 consecutive STEMI patients with no preexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 39 publications
(32 reference statements)
1
37
0
1
Order By: Relevance
“…Investigation of transaminases prognostic role in 2417 patients after percutaneous coronary intervention because of myocardial infarction showed that increase of ALT level correlated with stenosis of anterior interventricular artery and RCA. Increase of ALT concentration in these patients was associated with increased mortality immediately after intervention and in the remote period [5].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation of transaminases prognostic role in 2417 patients after percutaneous coronary intervention because of myocardial infarction showed that increase of ALT level correlated with stenosis of anterior interventricular artery and RCA. Increase of ALT concentration in these patients was associated with increased mortality immediately after intervention and in the remote period [5].…”
Section: Resultsmentioning
confidence: 99%
“…Проаналізували 35 клініко-лабораторних та інструментально-діагностичних показників 98 пацієнтів із верифікованою ІХС (40 % -гострий інфаркт міокарда, 60 % -нестабільна стенокардія; 79 % чоловіків і 21 % жінок; середній вік -61,7 ± 1,6 року), яких поділено на групи залежно від стану ЖМ: інтактний (29); сладж і холестероз (13); перегини тіла (13); деформації шийки та холецистит (27); холелітіаз (11); холецистектомія в анамнезі (5), за допомогою кореляційного аналізу. Ранжування стану ЖМ здійснено на підставі того, що зміни починаються зі сладжу та холестерозу, що за умов деформацій тіла та шийки ЖМ з утрудненням відтоку жовчі та скоротливості, призводять до холелітіазу, ускладнення якого є показанням до холецистектомії.…”
unclassified
“…Perhaps the biggest surprise in our nomogram is better correlation of pathological ventricular remodeling present 1 year after the myocardial infarction with AST than with CK (when CK is included instead of AST predictive value drops slighty, to approximately 88%). This can be attributed to statistical "glitch" due to low patient sample, but we believe that, since AST proved to be elevated after ischemic cell death of several other tissues, including kidney, skeletal muscle and brain, better correlation of AST is due to it being a marker of ishaemic end organ damage in acute coronary syndrom and not dominantly a marker of myocardial lesion (8)(9)(10)(11)(12). It is also noted that myocardial infarction affecting left anterior descending coronary artery is associated with the highest risk of adverse clinical outcomes because of the large amount of myocardial territory supplied by the LAD compared to other coronary arteries (13).…”
Section: Roc Analysis Found Great Predictive Value Of the Nomogrammentioning
confidence: 99%
“…erefore, ALT represents a specific biomarker for hepatocellular injury. Previous evidences showed that high levels of ALT were reversely associated with short-and longterm outcomes in patients with myocardial infarction [9,10]. Several other studies elucidated that elevated ALT was also associated with a higher prevalence of triple vessel CAD [11].…”
Section: Introductionmentioning
confidence: 98%